Cruising through a pandemic: The impact of COVID-19 on intentions to cruise. (March 2021) - Holland, Jennifer; Mazzarol, Tim; Soutar, Geoffrey N.; Tapsall, Suellen; Elliott, Wendy A.
Highlights: Country of residence significantly influences risk perceptions and affects future intentions to cruise. Media portrayal of cruising in Australia amplified risk perceptions about cruising. Cruise experience did not have a positive effect on cruise intentions and this is significantly different than previous studies. Both cruisers and non-cruisers were negative towards taking a cruise in the future and most said they will not travel until there is a vaccine. Impacts of COVID-19 and the cruise industry are identified and discussed within the Social Amplification of Risk Framework. Abstract: The global coronavirus pandemic has devastated the cruise sector with widespread disruption and cancellations affecting millions of cruise passengers. The cruise industry was negatively affected due to the enclavic and confined environment onboard, the high infection rates among both crew and passengers, and widespread negative media coverage. This study explores the impact of COVID-19 on willingness to cruise and attitudes towards cruising for both cruisers and non-cruisers living in Australia and the United Kingdom. Data analysis of respondents' comments was undertaken using both Leximancer text analytic software and manual content analysis. Findings indicate country of residence has a significant influence on risk perceptions for a cruise holiday and affects future intentions to cruise. Specific impacts for the cruise industry are discussed and recommendations proposed for policy and practice.